2014
DOI: 10.5941/myco.2014.42.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Microcyle Conidiation in Filamentous Fungi

Abstract: The typical life cycle of filamentous fungi commonly involves asexual sporulation after vegetative growth in response to environmental factors. The production of asexual spores is critical in the life cycle of most filamentous fungi. Normally, conidia are produced from vegetative hyphae (termed mycelia). However, fungal species subjected to stress conditions exhibit an extremely simplified asexual life cycle, in which the conidia that germinate directly generate further conidia, without forming mycelia. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The even distribution at the cell periphery is in agreement with its proposed localization in the plasma membrane in Aspergillus nidulans ( Taheri-Talesh et al, 2008 ). Using eGFP-ZtSso1 confirmed previous observations that Z. tritici macropycnidiospores are multi-cellular ( Steinberg, 2015 ) and grow by lateral “budding”, a process named “microcycle conidiation” ( Jung et al, 2014 ; Fig.4 D). The localization in the plasma membrane was further confirmed by co-visualization of eGFP-ZtSso1 and the lipophilic probe FM4-64 ( Fig.4 E), which enters the fungal plasma membrane before uptake into the cell ( Fischer-Parton et al, 2000 , Wedlich-Söldner et al, 2000 ).…”
Section: Resultssupporting
confidence: 80%
“…The even distribution at the cell periphery is in agreement with its proposed localization in the plasma membrane in Aspergillus nidulans ( Taheri-Talesh et al, 2008 ). Using eGFP-ZtSso1 confirmed previous observations that Z. tritici macropycnidiospores are multi-cellular ( Steinberg, 2015 ) and grow by lateral “budding”, a process named “microcycle conidiation” ( Jung et al, 2014 ; Fig.4 D). The localization in the plasma membrane was further confirmed by co-visualization of eGFP-ZtSso1 and the lipophilic probe FM4-64 ( Fig.4 E), which enters the fungal plasma membrane before uptake into the cell ( Fischer-Parton et al, 2000 , Wedlich-Söldner et al, 2000 ).…”
Section: Resultssupporting
confidence: 80%
“…In addition, conidia germinated, and the germ tubes directly produced a conidiophore and phialides, which formed two or three conidia (Figure 1(e)). This phenomenon, termed microcycle conidiation, is well known in fungi (Hanlin 1994;Jung et al 2014).…”
Section: Epiphytic Growth and Microcycle Conidiationmentioning
confidence: 98%
“…The hyphae were characterized by cylindrical terminal phialides (a), as well as by discreet intercalary phialides with very short necks (b) and slightly flaring collarettes (c). In some cases evidence of microcycle conidiation, as described by Jung et al (2014) was observed (d). c Light micrographs of C. pulveracea CBS110471 in submerged cultures, prepared with yeast peptone dextrose broth, showing hyphal growth, as well as yeastlike microcycle conidiation (e) for a number of fungi capable of microcycle conidiation (Pažout and Schröder 1988;Hanlin 1994;Boualem et al 2014;Jung et al 2014).…”
Section: Discussionmentioning
confidence: 93%
“…In some cases evidence of microcycle conidiation, as described by Jung et al (2014) was observed (d). c Light micrographs of C. pulveracea CBS110471 in submerged cultures, prepared with yeast peptone dextrose broth, showing hyphal growth, as well as yeastlike microcycle conidiation (e) for a number of fungi capable of microcycle conidiation (Pažout and Schröder 1988;Hanlin 1994;Boualem et al 2014;Jung et al 2014). It must be noted, however, that such transfer to a liquid medium, and the subsequent switch to microcycle conidiation as recorded in literature, was usually accompanied by other changes in the physico-chemical characteristics of the medium such as shifts in temperature, pH or nutrient composition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation